Música autoral, identidade e mercado de trabalho: a atuação do coletivo entreautores na região central do Rio Grande do Sul - Visentini, Íngrid Schmidt (2023)
This research deals with EntreAutores Collective, present in the city of Santa Maria/RS, as a space dedicated to the construction of collective identities and to promote strategies to integrate musicians in the local music market. It is an investigation of the collective, from its members, who are the subjects of the research: authorial musicians who organize themselves independently. The investigation consists of a case study, aiming to understand how the path to careers in the local music scene is made possible, seeking to verify to what extent authorial musicians have, or not, a remunerative activity exclusively associated with music, and other possible characteristics, such as such as: the desire of authorial musicians to act exclusively in the music market, what activities they carry out in addition to music, if they have other paid activities, what difficulties are present in the music market, if EntreAutores Collective changes the scenario of the music market by expanding possibilities. All these analyzed aspects indicate the presence of professional socialization: a learning constituted from the interaction between those involved. This sociability component favors not only building relationships, learning and sharing worldviews. It is from socialization that the shared ways of being and existing constitute a politicized reading of professional performance and, also, of the Collective itself.